Dense graphene foam and hexagonal boron nitride filled PDMS composites with high thermal conductivity and breakdown strength. (10th November 2017) - Fang, Haoming; Zhang, Xiao; Zhao, Yunhong; Bai, Shu-Lin
Abstract: In the present study, high thermally conductive and electrically insulated polymer composites containing modified dense graphene foam (MGF) and modified hexagonal boron nitride (M-h-BN) via polydopamine (PDA) coating and 3-aminopropyltriethoxysilane (APTS) grafting were manufactured and studied. Due to the double percolated networks built by MGF and M-h-BN, the polydimethylsiloxane (PDMS) matrix composite has high thermal conductivity of 23.45Wm −1 K −1 and 2.11Wm −1 K −1 in in-plane and out-of-plane directions, respectively. In addition, an insulated layer of M-h-BN/PDMS can be introduced onto both sides of composite sample with the help of infiltration technique, which results in a high breakdown strength of 4.5 kV/mm. Owing to the excellent comprehensive properties, the M-h-BN/MGF/PDMS composite has a promising application in heat management field of the microelectronic industry.